2014
DOI: 10.1111/1475-679x.12060
|View full text |Cite
|
Sign up to set email alerts
|

Do Joint Audits Improve or Impair Audit Quality?

Abstract: Conventional wisdom holds that joint audits would improve audit quality by enhancing audit evidence precision because “Two heads are better than one.” Our paper challenges this wisdom. We show that joint audits by one big firm and one small firm may impair audit quality, because, in that situation, joint audits induce a free‐riding problem between audit firms and reduce audit evidence precision. We further derive a set of empirically testable predictions comparing audit evidence precision and audit fees under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 43 publications
3
61
0
2
Order By: Relevance
“…Deng et al. () model the effect of joint audits on audit fees, audit evidence precision, and auditor independence. They compare two types of joint auditor pairs, Two Big‐Firm Auditors (BB) and One Big‐Firm Auditor paired with one Small‐Firm Auditor (BS), with One Big‐Firm Auditor (B).…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Deng et al. () model the effect of joint audits on audit fees, audit evidence precision, and auditor independence. They compare two types of joint auditor pairs, Two Big‐Firm Auditors (BB) and One Big‐Firm Auditor paired with one Small‐Firm Auditor (BS), with One Big‐Firm Auditor (B).…”
Section: Related Researchmentioning
confidence: 99%
“…Deng et al. () neither directly compare auditor independence between BB and BS pairs nor consider the effect of coordination on the performance of joint auditor pairs.…”
Section: Related Researchmentioning
confidence: 99%
“…Meanwhile, foreign share firms with dual audit experience did not show much change in the distribution of risk-aversion, even after the dual audit system was abolished. That is, there was no change in the number of small loss enterprises, and the number of small profit enterprises increased by only 6.67% (8), even after the end of the dual audit system.…”
Section: Robustness Test 2: Loss Aversionmentioning
confidence: 96%
“…Because a joint audit model requires two independent auditors to jointly issue a unified audit report, when the audit fails, the responsibilities of the two auditors cannot be clearly identified, which is the most obvious disadvantage of a joint audit. Deng et al [8] and other researchers found that a joint audit has always resulted in the phenomenon that auditors with lower competence get a "free ride" by relying on the auditors with higher competence; this weakens auditing independence, since an audit report issued jointly by two independent auditors of different capabilities is the result of mutual negotiation. In 2003, the South Korean Government also considered introducing a joint audit model, but it was never implemented because no relevant measures could be proposed to clarify the responsibilities between the auditors.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation